2018
DOI: 10.1016/j.jagp.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil Treatment in Patients With Depression and Cognitive Impairment on Stable Antidepressant Treatment: A Randomized Controlled Trial

Abstract: The results do not support adjunctive off-label cholinesterase inhibitor treatment in patients with depression and cognitive impairment. The findings highlight the need to prioritize discovery of novel treatments for this highly prevalent population with comorbid illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 42 publications
(51 reference statements)
1
27
0
Order By: Relevance
“…5,6 Moreover, cognitive enhancers only have a modest and inconsistent effect on cognitive decline in this population. 7,8 One study assessed the combination of donepezil with standard antidepressant maintenance in preventing cognitive decline in older patients with remitted MDD. 7 The addition of donepezil had a modest and temporary (one-year) effect on global cognition but it was associated with a higher rate of depressive relapse (35%) than placebo (19%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Moreover, cognitive enhancers only have a modest and inconsistent effect on cognitive decline in this population. 7,8 One study assessed the combination of donepezil with standard antidepressant maintenance in preventing cognitive decline in older patients with remitted MDD. 7 The addition of donepezil had a modest and temporary (one-year) effect on global cognition but it was associated with a higher rate of depressive relapse (35%) than placebo (19%).…”
Section: Introductionmentioning
confidence: 99%
“…7 In another study, donepezil did not show any cognitive benefits in patients with depression and mild cognitive impairment (MCI). 8 Thus, there is a need for interventions that slow or prevent cognitive decline in older patients with MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our results in the current study, depression was found to be common among patients with MCI and cognitive de cits [25], placing those patients at higher risk for dementia in their later years. This combination of depression and MCI complicates the health condition of these patients at later stages of life, particularly affecting their treatment for combating cognitive decline, such as donepezil for Alzheimer's disease as reported by Devanand and colleagues [26].…”
Section: Discussionmentioning
confidence: 97%
“…Similar to our results in the current study, depression was found to be common among patients with MCI and cognitive de cits [30], placing those patients at higher risk for dementia in their later years. This combination of depression and MCI complicates the health condition of these patients at later stages of life, particularly affecting their treatment for combating cognitive decline, such as donepezil for Alzheimer's disease as reported by Devanand and colleagues [31].…”
Section: Discussionmentioning
confidence: 97%